Workload consolidation techniques to optimise energy in cloud: review. (2017) - Sanjeevi, P.; Viswanathan, P.
The major issue threatening the cloud computing is that it consumes an enormous amount of energy for providing valuable computational services. Many workload consolidation attempts were taken to reduce the energy consumption of data centre. Broad research on all workload consolidation issues in the cloud environment is extremely challenging since it entails developers to deliberate network setup and the cloud environment, which could be beyond the control. Moreover, the consolidation of workload cannot be predicted or restrained. Though, existing literature lacks the crucial agility for workload consolidation to reduce energy in cloud data centre, producing poor responsiveness and inadequate scalability. In this paper, we present the background and motivation of workload consolidation techniques in the cloud. Moreover, we acquaintance four recent workload consolidation algorithms considering metrics for reducing energy and the features of the best workload consolidation algorithm is highlighted. Finally, research areas and challenges are boasted based on the strengths and weakness of prevailing workload consolidation methods.